Simultaneous determination of primaquine and carboxyprimaquine in plasma using solid phase extraction and LC-MS assay - Page-Sharp, Madhu; Ilett, K.; Betuela, I.; Davis, T.; Batty, Kevin (Elsevier, 2012)
Sensitive bioanalytical methods are required for pharmacokinetic studies in children, due to the small volume and modest number of samples that can be obtained. We sought to develop a LC–MS assay for primaquine and its active metabolite, carboxyprimaquine, following simultaneous, solid phase extraction of both analytes from human plasma. The analysis was conducted on a single-quad LC–MS system (Shimadzu Model 2020) in ESI+ mode, with quantitation by selected ion monitoring. Primaquine, carboxyprimaquine and 8-aminoquinoline (internal standard) were separated using a mobile phase of 80:20 methanol:water with 0.1% (v/v) formic acid and a Luna C18 HPLC column, at ambient temperature. Solid phase extraction of the analytes from plasma (0.5 mL) was achieved with Oasis® HLB cartridges. The retention times for primaquine, 8-aminoquinoline and carboxyprimaquine were 3.3, 5.7 and 8.5 min, respectively. The calibration curve range (2–1500 μg/L) was appropriate for the limits of quantification and detection for primaquine (2 μg/L and 1 μg/L, respectively) and carboxyprimaquine (2.5 μg/L and 1 μg/L) and the anticipated plasma concentrations of the analytes. Intra- and inter-day precision for both primaquine and carboxyprimaquine was <10% across the concentration range 5–1000 μg/L. Accuracy for both analytes was <15% (5–500 μg/L). This validated LC–MS method with solid phase extraction facilitates the simultaneous analysis of primaquine and carboxyprimaquine from small volumes of human plasma, with run time <10 min, recovery >85% and sensitivity of 1–2 μg/L.